Intervenções analítico-comportamentais para a esquizofrenia: uma revisão sistemática da literatura - Bandeira, Vitória Grídvia (2017)
The present study presents a systematic review from the behavior analytic literature for schizophrenia treatment between 1960 to 2016. There were used these following data base: PsycINFO, Science Direct, PubMed, Lilacs, Pepsic, Banco Digital de Teses e Dissertações and were used these scientific journals: Revista Brasileira de Análise do Comportamento, Comportamento em Foco and Sobre Comportamento e Cognição. The sample were composed of 46 studies, in majority, adopted behavioral deficit/excess as a participant selection criteria. There was found a diminish in foreign publications and a concentration in non published national studies. Interventions, in majority, had a duration between 1 to 3 mouths, used male subjects and were conducted by the experimenters. Overall, the studies target one class responses, which were directly observed. Few reviewed studies involved staff training, generalization planning and evaluation and following measures. It was found that more recent studies had used experimental manipulations to test variables controlling behavior problems and doing interventions in alternative environments others than psychiatry hospitals. As the years gone by, there was a diminish in the use of aversive consequences and in the tangible consequences exclusive programming and there was a raise for the use of social consequences. It’s was found that the behavior analytic procedure used were followed by successful results, although it cannot be point out which one was better than the others. It is suggested more studies to fill the gaps pointed out in the present study in order to give a more consistent bias for the behavior analytic approach for schizophrenia treatment